(untitled) (Revista Brasileira Multidisciplinar, 2024)
Chamomile oil (Matricaria chamomilla L.) has calming, anti-inflammatory, and antibacterial properties, promising to accelerate the healing process. Therefore, this study aimed to develop gels-creams containing chamomile oil and evaluate the bioadhesive and occlusive potential, antioxidant activity, and cytotoxicity in an Allium cepa assay, aiming for cutaneous application. The formulations were prepared by emulsification, using two phases: an oily phase composed of emulsifiers and chamomile oil and an aqueous phase containing gellan gum (F1) or carrageenan gum (F2) as a gel-forming agent. Bioadhesion was conducted with porcine skin as a biological membrane, with similarities between the formulations. For in vitro occlusion, the water loss method was used. Both have occlusivity of approximately 30%. Antioxidant activity evaluated the scavenging capacity of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical. In this test, there was a difference between the formulations, where F1 showed an activity of 82.28 ± 13.04% and F2 of 61.51 ± 7.50%. The Allium cepa model was used to evaluate cytotoxicity. Both formulations reduced the mitotic index compared to the negative control, suggesting possible toxicity at the concentration tested. The gel-creams developed in this study, using natural gums, proved to be promising platforms for the cutaneous administration of chamomile oil. The results of bioadhesion, occlusion, and antioxidant activity suggest that the formulations have a potential for application to skin wounds, especially those caused by burns, as they could accelerate recovery and promote patient comfort.